Epidemiological Study of Acute Unintentional Poisoning Among Children in Iran - Tarhani, Fariba; Nezami, Alireza; Heidari, Ghobad; Hosseinizadeh-salavati, Nazanin (Drug Research, 2022)
The occurrence of different types of poisoning and early diagnosis is important for therapeutic measures. In this study, we investigate the epidemiological causes of acute poisoning in children.In this retrospective descriptive study, children presented with acute poisoning during 2010–2019 to Shahid Madani Hospital were included. The Electronic Medical Record system of the hospital was accessed to obtain the data of the patients. The data included was demographic information, type of poisoning, clinical findings, complications, duration of hospitalization, parents’ education status, and mortality status.Of 336 patients included in the study, the mean age of patients was 4.90±3.27 years (range: 1–12 years). There was a significant correlation between the age of the child and the type of poisoning, p=0.001. The most frequent age group was 5 years and less (69.6%). The most frequent sex group was male (58.6%). However, there was no significant correlation between the sex of the child and the type of poisoning. Parents’ education and ICU admission were also associated significantly with the type of poisoning, p=0.001, respectively. The most common type of poisoning in children was medication (60.6%) which was mainly due to methadone. The mortality rate in the study was 1.2%.Our study showed that pharmacological drugs are the main cause of poisoning in our population. Age of the children is likely to be associated with the type of poisoning however, no gender difference was found in this regard was found in our study.
Keywords: alcohols/ethanol; analgesic drugs; drug research